Antibacterial Effects of Antiretrovirals, Potential Implications for Microbiome Studies in HIV. Issue 1 (January 2018) - Shilaih, Mohaned; Angst, Daniel C; Marzel, Alex; Bonhoeffer, Sebastian; Günthard, Huldrych F; Kouyos, Roger D
Background: Despite being used by more than 18 million people our understanding of the extent of the effects of antiretrovirals on the human body and other organisms remains incomplete. In addition, the direct effect of antiretrovirals on the gut microbiota of HIV-infected individuals has been largely overlooked in microbiome studies concerned with HIV-infected individuals. Methods: Here we tested 25 antiretrovirals on Bacillus subtilis and Escherichia coli using a broth microdilution assay to assess whether these drugs have an antibacterial effect. Results: We found that several widely used antiretroviral drugs have in vitro antibacterial activity against both gram-positive and gram-negative commensal bacteria. Efavirenz inhibited the growth of B. subtilis with a minimum inhibitory concentration (MIC) of 16 μg/ml (in all three replicates), while 2', 3'-dideoxyinosine and zidovudine inhibited the growth of E. coli with an MIC of 16–32 μg/ml and 0.016–0.125 μg/ml (respectively). Conclusions: Given the large and increasing number of individuals on antiretrovirals, and the lifelong nature of HIV treatment, this proof-of-concept report could have several potential implications, including an impact of antiretrovirals on bacterial coinfections, as well as potentials for drug discovery and repositioning.